+0  
 
0
83
1
avatar

https://prnt.sc/qd7nik

 

thank you 

 Dec 19, 2019
 #1
avatar+109563 
+2

y asymptote  ⇒   CORRECT   !!!

 

x asymptotes 

 

x^2  + 2x  - 3                  ( x + 3) ( x - 1)               (x + 3)

___________  =            ______________ =   ________

2x^2  - x   - 1                  (2x + 1) ( x - 1)             (2x + 1)

 

 

x = 1/2   is also CORRECT!!!!!

 

GOOD JOB!!!

 

[We have a "hole"  at   x = 1    ]

 

 

cool cool cool

 Dec 19, 2019
edited by CPhill  Dec 19, 2019

20 Online Users